Final Cut Pro X Guru: Motion Graphics in Motion and After Effects. - Harauz, Nick (linkedin.com, 2016)
Final Cut Pro guru Nick Harauz shows how to create motion graphics using Final Cut Pro X, Motion, and After Effects.